Pengaruh Kreativitas Guru Terhadap Minat Belajar Mata Pelajaran IPS Siswa SMP Negeri 14 Banda Aceh - Nazila Ulfa; A. Hamid; Ratna Mutia (Edupreneurship: Jurnal Pendidikan Ekonomi, 2025)
This study aims to analyze the influence of teacher creativity on students' interest in learning Social Sciences (IPS) subjects at SMP Negeri 14 Banda Aceh. This study uses a quantitative approach with a descriptive method. The research sample consisted of 35 students determined through a simple random sampling technique. The data collection instrument was a questionnaire that had been tested for validity and reliability. The results of a simple linear regression analysis showed that there was a positive and significant influence between teacher creativity on students' interest in learning, with a coefficient of determination (R2) of 0.332. This indicates that 33.2% of the variation in students' interest in learning can be explained by teacher creativity, with a significance value of 0.000 <0.05. It can be concluded that the higher the level of teacher creativity in the learning process, the higher the students' interest in learning. Therefore, it is suggested that teachers always develop creativity in learning in order to create an innovative and participatory learning atmosphere.